2016
DOI: 10.1152/physiolgenomics.00058.2016
|View full text |Cite
|
Sign up to set email alerts
|

Serum response factor provokes epithelial-mesenchymal transition in renal tubular epithelial cells of diabetic nephropathy

Abstract: We investigated the role of serum response factor (SRF) in epithelial-mesenchymal transition (EMT) of renal tubular epithelial cells (TECs) in diabetic nephropathy (DN). The expression of SRF, epithelial markers (E-cadherin and ZO-1), and mesenchymal markers (fibronectin, collagen-1, α-SMA, FSP-1) was examined in human proximal renal tubular epithelial cells (HK-2 cells) or renal medulla tissues following high glucose. SRF was upregulated by SRF plasmids and downregulated by CCG-1423 (a small molecule inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 30 publications
0
20
1
Order By: Relevance
“…He et al (35) demonstrated that SRF promotes EMT in human peritoneal mesothelial cells. SRF also provokes EMT in renal tubular epithelial cells of diabetic nephropathy (36), and it induces EMT in hepatocellular carcinoma, prostate cancer, and gastric cancer (37). Therefore, SRF has a significant role in EMT and cancer metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…He et al (35) demonstrated that SRF promotes EMT in human peritoneal mesothelial cells. SRF also provokes EMT in renal tubular epithelial cells of diabetic nephropathy (36), and it induces EMT in hepatocellular carcinoma, prostate cancer, and gastric cancer (37). Therefore, SRF has a significant role in EMT and cancer metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Although in vitro studies support the existence of EMT, evidence that fibroblasts derive from epithelial cells in vivo is controversial (44,45). However, recently Zhao et al (46) have reported both in vitro in tubular cells after high glucose treatment and in vivo in diabetic rats, the increase in mesenchymal markers (fibronectin, collagen-1, a-SMA, and fibroblast-specific protein-1) and the decrease in epithelial markers (E-cadherin and zonula occludens-1), thus concluding that HG plays an important role in EMT and in DN dysfunction. In addition, cytoskeletal alterations have been described to play an important role in EMT in breast cancer cells (47).…”
Section: Discussionmentioning
confidence: 99%
“…This is a synthetic compound originally identified as an inhibitor of the small GTPase RhoA 174 , but nowadays accepted as an inhibitor of SRF-dependent responses 175178 . SRF is a transcription factor considered as a master regulator in both cancer and embryonic development 179 .…”
Section: Micalmentioning
confidence: 99%